Role of intravenous urogram in investigation of urinary tract infection: an observational study. Issue 945 (14th July 2004) - Padmakumar, B; Carty, H M; Hughes, D A; Judd, B A
Abstract : Objectives: To examine the value of an intravenous urogram (IVU) in patients with abnormal differential 99m Tc dimercaptosuccinic acid (DMSA) uptake without scarring or ultrasound abnormality. Study design: Forty patients (age 0–19 years) were identified over a two year period in whom the differential renal uptake was >10%, who had smooth renal outlines, and had no evidence of scarring. All patients had an ultrasound examination. Two had marked urological abnormalities on ultrasound and eight had a duplex system in the kidney with greater DMSA uptake. In 18 patients where no explanation was apparent for the discrepant DMSA uptake, an IVU was performed. Results: Eight patients had a normal IVU. In the remaining 10 patients, six had duplex systems without scarring and four had appearances of scarring in the kidney with reduced DMSA uptake. Conclusions: In this small selected group an IVU will identify a significant number of patients with normal kidneys, unrecognised simple duplex systems, or scarring where the DMSA scan has been inconclusive. This will help in planning long term follow up.